EKSPLORASI DAN IDENTIFIKASI MIKORIZA DARI BERBAGAI MACAM VEGETASI PADA LAHAN AGROFORESTRY - Jessica Maria Purba; Budi Prasetya (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
Soil fertility degradation has been accelerated by the heavy use of inorganic fertilizers for a long time, especially in agroforestry lands of Sumbermanjing Wetan, Malang, East Java. This study was aimed to find out arbuscular mycorrhizae that can be used for improving soil fertility. This study was conducted by purposive random sampling continued by randomized block design with the measured variables were basal area, canopy, number of spores, percentage of root mycorrhizal colonization, soil pH, soil C-organic, available P, litterfall, and types of spores. The results showed that the most common type of spore found was Glomus sp. The spore populations depended on vegetation and were most commonly found in Albicia falcataria. The soil pH of agroforestry land ranged from 5.1 to 5.4, organic carbon content ranged from 3.43 to 4.04%, and available P content ranged from 7.7-9.9 kg P2O5 ha-1. Vegetation affected the soil physicochemical and biological properties.